Time-Chunking and Hyper-Refocusing in a Digitally-Enabled Workplace: Six Forms of Knowledge Workers - Gaskin, James E.; Skousen, Tanner (Frontiers in Psychology, 2016)
Until the turn of the millennium, switching tasks required moving locations or reconfiguring physical workspaces. However, contemporary digital tools and workspaces allow knowledge workers to perform an increasingly diverse set of tasks, with an increasingly extending arm of influence, all from the same physical location without any physical reconfigurations or traversing of physical space. Along with this increased ambidexterity comes an increase in the quantity and frequency of demands on the time of knowledge workers. This digitalization of work now tethers their ability to perform largely to their ability to intensely focus in small chunks, and then “hyper-jump” that focus to another task without traversing the cognitive cool downs or warm ups required to reconfigure their train of thought from one task to another. Accordingly, they must become more like the hyper-functioning tools they employ if they are to avoid becoming the bottleneck resource in the configuration of socio-technical elements comprising their work routines. In order to better understand how knowledge workers manage their time and maintain focus across multiple and interrupting tasks, we leverage current time prioritization literature to propose and theorize around two key constructs: time-chunking and hyper-refocusing. By combining the possible values for these two constructs, we hypothesize the emergence of six forms of knowledge workers and their relative expected performance. The effects of digitalization on these new worker forms are discussed. We conclude by discussing opportunities for new research questions regarding time-chunking strategies and the hyper-refocusing ability.